Enhancing ROS 2 (robot operating system 2) security with standardized post-quantum cryptosystems - Safdar, Umair; Qadir, Sana; Nazir, M. Saqib (International journal of information security, 2025)
The global race for quantum computers has sparked significant interest in the integration of quantum-secure cryptographic algorithms into traditional applications. However, relatively limited work has been done on adapting and assessing the utilization of Post Quantum (PQ) algorithms in industrial/robotics applications that run on constrained IoT devices. This work aims to fill this gap by fully integrating the communication middleware Data Distribution Service (DDS) of Robot Operating System (ROS) 2 with the recently standardized National Institute of Standards and Technology (NIST) PQ cryptographic algorithms. It also evaluates the performance of this PQ enhanced DDS on constrained devices (Raspberry Pi 5) using time-based and size-based metrics. The findings highlight the feasibility of using PQ algorithms, especially module lattice-based algorithms, by showing their competitive results with 128- and 256-bit classical cryptographic algorithms. Overall, this work represents a significant step towards future-proofing ROS 2 systems against quantum threats and offering insights into the impact of post-quantum cryptography on performance of resource constrained setups. In the long run, this could ease the transition to post-quantum cryptography and play a vital role in securing safety-critical systems such as energy, communications, transport, and power.